Atrial Flutter or Fibrillation is the Most Frequent and Life‐Threatening Arrhythmia in Myotonic Dystrophy. Issue 3 (9th October 2013) - BREMBILLA‐PERROT, BÉATRICE; SCHWARTZ, JÉRÔME; HUTTIN, OLIVIER; FRIKHA, ZIED; SELLAL, JEAN MARC; SADOUL, NICHOLAS; BLANGY, HUGUES; OLIVIER, ARNAUD; LOUIS, SARAH; KAMINSKY, PIERRE
<x xml:space="preserve">Abstract</x> Background Several arrhythmias were reported in myotonic dystrophy (MD). Objectives To evaluate the prevalence of atrial fibrillation (AF) and atrial flutter (AFL) in MD and the clinical consequences. Methods One hundred sixty‐one patients, mean age 41 ± 14 years, were referred for a type 1 MD. All patients were asymptomatic except four patients and followed during 5 ± 4 years. Electrocardiogram (ECG), echocardiography assessing left ventricular ejection fraction, and Holter monitoring were obtained and repeated. Results Twenty‐seven patients (17%) presented sustained (>1 hour) AF (n = 15) or AFL (n = 12); two of them presented syncope‐related 1/1 AFL. In one of them, 16 years of age, cardiac defibrillator was implanted for a diagnosis of ventricular tachycardia, but the true diagnosis was established after inappropriate shocks. AFL ablation was performed in five patients, but four developed AF. The other seven patients with AFL developed AF. During the follow‐up, 22 patients died (14%) from cardiac and respiratory failure; eight patients with AF/AFL died (30%) while only 14 without AF/AFL died (10%; P < 0.01). Univariate analysis indicated that age >40 years (death: 48 ± 14 vs 40 ± 8 in alive patients), abnormal ECG, and occurrence of AF/AFL were significant factors of death. At multivariate analysis, AF at ECG (odds ratio: 3.12) and age >40 (odds ratio: 3.14) were the sole independent variables predicting death. Conclusions AF and AFL were frequent in MD and increased mortality. AFL could present as 1/1 AFL with a poor tolerance and a risk of misdiagnosis despite frequent conduction disturbances. This arrhythmia could explain wide QRS tachycardia occurring in MD and interpreted as VT.